ST18 affects cell–cell adhesion in pemphigus vulgaris in a tumour necrosis factor‐α‐dependent fashion. (4th January 2021) - Assaf, S.; Malki, L.; Mayer, T.; Mohamad, J.; Peled, A.; Pavlovsky, M.; Malovitski, K.; Sarig, O.; Vodo, D.; Sprecher, E.
Summary: Background: Pemphigus vulgaris (PV) is a life‐threatening mucocutaneous autoimmune blistering disease. We previously showed that genetic variants within the ST18 gene promoter area confer a sixfold increase in the propensity to develop PV. ST18, a transcription factor, was found to be overexpressed in the epidermis of patients with PV. In addition, it was found to promote autoantibody‐mediated abnormal epidermal cell–cell adhesion and secretion of proinflammatory mediators by keratinocytes. Objectives: To delineate the mechanism through which ST18 contributes to destabilization of cell–cell adhesion. Methods: We used quantitative reverse‐transcriptase polymerase chain reaction, immunofluorescence microscopy, a luciferase reporter system, site‐directed mutagenesis, chromatin immunoprecipitation (ChIP) and the dispase dissociation assay. Results: The ChIP and luciferase reporter assays showed that ST18 directly binds and activates the TNF promoter. Accordingly, increased ST18 expression contributes to PV pathogenesis by destabilizing cell–cell adhesion in a tumour necrosis factor (TNF)‐α‐dependent fashion. In addition, dual immunofluorescence staining showed increased expression of both ST18 and TNF‐α in the skin of patients with PV carrying an ST18‐associated PV risk variant, which was found to be associated with a more extensive PV phenotype. Conclusions: Our findings suggest a role for TNF‐α in mediating the deleterious effect of increased ST18 expression in PV skin. Abstract : What is already known about this topic? Pemphigus vulgaris (PV) is a blistering disease that results from autoantibody‐mediated destabilization of cell–cell adhesion in the epidermis. Genetic variations within the promoter of the ST18 gene are associated with the propensity to develop PV. ST18 is overexpressed in the skin of patients with PV and promotes autoantibody‐mediated abnormal epidermal cell–cell adhesion. ST18 has been shown to stimulate PV autoantibody‐mediated secretion of tumour necrosis factor (TNF)‐α by epidermal keratinocytes. What does this study add? ST18 stimulates the promoter activity of TNF, encoding TNF‐α. ST18 promotes PV serum‐mediated acantholysis in a TNF‐α‐dependent manner. Patients with PV carrying an ST18‐associated risk variant for PV demonstrate concomitant increased expression of both ST18 and TNF‐α in the epidermis, as well as a more extensive and severe PV phenotype. What is the translational message? Risk variant genotyping of ST18 and TNF may predict which patients with PV are more likely to respond to TNF‐α‐blocking agents. Linked Comment:  Hashimoto. Br J Dermatol 2021; 184 :1001–1002 .